TRAVEL MODE CHOICE MODELING WITH A COMBINATION OF STATED AND REVEALED PREFERENCES: A CASE STUDY OF MAKASSAR CITY - Fitri Taufik, Yushalihah
The use of private vehicles by the community is increasing along with the increase in population and economic activities causing increased traffic congestion. The irregular time management of BRT and low public interest in using BRT as indicated by the low load factor which is expected to be a solution to congestion have an impact on the failure and cessation of BRT operations. This makes the issue of an imbalance between supply and demand for transportation in Makassar City. This study aims to model the choice of modes in order to determine the potential demand for mass public transportation in supporting the policy of developing public transportation in Makassar City. The alternative modes of choice in this study include the available modes of transportation and the situation of new or different options including city transportation (pete-pete), BRT, online taxis, online motorcycle taxis, private cars, and private motorbikes. This study uses a disaggregated approach with multinomial logit and nested logit analysis methods with Biogeme 2.4 software to determine the factors that influence mode choice preferences as well as probability and elasticity analysis to determine the probability of choosing a mode in general and with changes in the value of the influential variable. The factors that influence the choice of travel mode are travel time, travel costs, headway, gender, age, last education (S1 and >S1), occupation (not working, ASN/BUMN/BUMD, private employees, self-employed, and honorariums). /contract worker), income, dependents/children (none, 1-2 people, and 3-4 people), private car ownership, private motorbike ownership, bicycle ownership, SIM A ownership, SIM C ownership, time of trip ( 1-6 days ago), purpose of travel (business/work and education), use of existing modes (private car, online taxi, city transportation/pete-pete, and private motorbike), perception of mode reliability and environmental awareness, perception of comfort and security, and selfselection. The probabilities of alternative modes obtained include city transportation (pete-pete) by 5%, BRT by 11%, online taxis by 3%, online motorcycle taxis by 4%, private cars by 24%, private motorbikes by 52%, and none 1% choice. The most elastic alternative mode opportunities with changes in travel costs are BRT and private motorbikes so that they can be used to increase the use of BRT and reduce the use of private motorbikes. There is a potential demand for alternative modes of BRT as a mode of travel, there needs to be a feeder mode where there is potential for existing modes such as city transportation (pete-pete)iv considering the existing routes have reached several areas that cannot be reached by BRT.